2000
DOI: 10.1002/(sici)1098-2280(2000)35:3<253::aid-em11>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

In vivo transgenic mutation assays

Abstract: Transgenic rodent gene mutation models provide quick and statistically reliable assays for mutations in the DNA from any tissue. For regulatory applications, assays should be based on neutral genes, be generally available in several laboratories, and be readily transferable. Five or fewer repeated treatments are inadequate to conclude that a compound is negative but more than 90 daily treatments may risk complications. A sampling time of 35 days is suitable for most tissues and chemicals, while shorter samplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(64 citation statements)
references
References 44 publications
0
61
0
3
Order By: Relevance
“…Although, the micronucleus assay has been conventionally used (Heddle et al, 1983;Heddle et al, 1991;Kirsch-Volders et al, 2011), other tests such as those based on DNA adduct formation (Dybing et al, 1984), in vivo chromosomal aberration (You et al, 1993), transgenic mutation (Heddle et al, 2000;Lambert et al, 2005) and comet assay (Tice et al, 2000;Kumaravel and Jha, 2006;Olive and Banáth, 2006) have also been routinely employed in the past as in vivo follow up assay when equivocal or inconclusive results are obtained in the in vitro assay. Kawaguchi et al (2010), reported an identical sensitivity of the micronucleus test and the comet assay in detecting the studied mutagens but were quick to point out that the power of the comet assay to detect a low level of genotoxic potential can be superior to that of micronucleus test by the inclusion of using DNA resynthesis inhibitors.…”
Section: Appropriate In Vivo Follow-up Assay Of Genotoxicitymentioning
confidence: 99%
“…Although, the micronucleus assay has been conventionally used (Heddle et al, 1983;Heddle et al, 1991;Kirsch-Volders et al, 2011), other tests such as those based on DNA adduct formation (Dybing et al, 1984), in vivo chromosomal aberration (You et al, 1993), transgenic mutation (Heddle et al, 2000;Lambert et al, 2005) and comet assay (Tice et al, 2000;Kumaravel and Jha, 2006;Olive and Banáth, 2006) have also been routinely employed in the past as in vivo follow up assay when equivocal or inconclusive results are obtained in the in vitro assay. Kawaguchi et al (2010), reported an identical sensitivity of the micronucleus test and the comet assay in detecting the studied mutagens but were quick to point out that the power of the comet assay to detect a low level of genotoxic potential can be superior to that of micronucleus test by the inclusion of using DNA resynthesis inhibitors.…”
Section: Appropriate In Vivo Follow-up Assay Of Genotoxicitymentioning
confidence: 99%
“…Le nombre optimal de plages ou de colonies par échantillon d'ADN dépend de la probabilité statistique de détecter des mutants en nombre suffisant à une fréquence de mutants spontanés donnée. En général, un minimum de 125 000 à 300 000 plages est nécessaire si la fréquence de mutants spontanés est de l'ordre de 3 x 10 -5 (15). Pour l'essai lacI (Big Blue ® ), il importe de démontrer que la gamme complète de phénotypes mutants de la couleur peut être détectée par inclusion de témoins de la couleur appropriée simultanément à chaque plage.…”
Section: Méthodes De Mesureunclassified
“…Les ateliers internationaux sur les essais de génotoxicité (IWGT) ont approuvé la prise en compte des essais pour la détection in vivo des mutations génétiques chez les RTG et ont recommandé un protocole de mise en application de ces essais (15) (29). La présente LD découle de ces recommandations.…”
Section: Introductionunclassified
“…The study was carried out under GLP. As formal technical guidelines for this type of study are not available, the study protocol was designed in conformity with principles for transgenic studies identified by international expert groups (Gorelick and Mirsalis, 1996;Heddle et al, 2000). The study was conducted in five groups, three of which received furfural by gavage in corn oil, one negative control group received vehicle alone and one positive control group received ethylnitrosourea (ENU).…”
Section: "Special Studies On Genotoxicitymentioning
confidence: 99%